Total Spinal Anesthesia Failure: Have You Assessed the Sensory Anesthesia in Sacral Dermatomes? - Sa Oliveira, Ronaldo Rodrigo de [UNESP]; Modolo, Marilia Pinheiro [UNESP]; Mizubuti, Glenio Bitencourt; Ho, Anthony M. H.; Moreira de Barros, Guilherme Antonio [UNESP]; Silva, Leopoldo Muniz da; Braz, Leandro Gobbo [UNESP]; Pinheiro Modolo, Norma Sueli [UNESP]; Day, Andrew G.; Phelan, Rachel; Navarro e Lima, Lais Helena [UNESP]; Ganem, Eliana Marisa [UNESP] (Lippincott Williams & Wilkins, 2017)
Intrathecal local anesthetic maldistribution is a well-known cause of spinal anesthesia failure (SAF). This could potentially result in sensory blockade restricted to the sacral dermatomes. We sought to determine the overall incidence of SAF and the role of sacral dermatomes in differentiating between total and partial failures. Of the 3111 spinals prospectively examined, 194 (6.2%) were classified as failures. Of the 72 presumed total failures based on the initial assessment, evaluation of the sacral dermatomes revealed sensory blockade in 32 (44%; 95% confidence interval, 32.7%-56.6%). Sacral dermatome assessment after SAF may be important in safely guiding subsequent anesthetic management.